THE INFLUENCE OF DIFFERENT SOWING DATES ON THE BIOMETRIC INDICATORS OF DURUM WHEAT VARIETIES - J.B.Khudaykulov; I.Buriev (Journals Park Publishing, 2023)
This article presents data on the effect of sowing dates on biometric parameters of wheat varieties. According to the results of the above analysis, the longest spike length in the first planting period was 9.27 cm in the "Javakhir" variety, and the number of grains in one spike was 42 grains, and the average weight of 1000 grains was 38.7 grams.
Keywords: Sowing date, durum wheat, cultivars, spike length, grain number, grain weight, thousand grain weight.